Selected Aspects of the Professional Beliefs of Novice Teachers - Sevcikova, Jaroslava; Plischke, Jitka (e-Pedagogium, 2020)
The authors of the study deal with the partial results of the longitudinal research focused on the analysis of selected aspects of professional beliefs formation of novice teachers. They seek to answer the question of how teachers themselves reflect and then interpret their mental representations to professional beliefs and how they view the aspects of its formation. The research was carried out by a qualitative design, the data that were obtained mainly from in-depth interviews and focus groups were subsequently subjected to open, axial and selective coding.
Keywords: professional beliefs; novice teacher; formation of professional beliefs; in-depth interviews; focus groups.